A new hybrid bacteriocin, Ent35–MccV, displays antimicrobial activity against pathogenic Gram-positive and Gram-negative bacteria - Acuña, Leonardo (2012)
Bacteriocins and microcins are ribosomally synthesized antimicrobial peptides that are usually active against phylogenetically related bacteria. Thus, bacteriocins are active against Gram-positive while microcins are active against Gram-negative bacteria. The narrow spectrum of action generally displayed by bacteriocins from lactic acid bacteria represents an important limitation for the application of these peptides as clinical drugs or as food biopreservatives. The present study describes the design and expression of a novel recombinant hybrid peptide combining enterocin CRL35 and microcin V named Ent35?MccV. The chimerical bacteriocin displayed antimicrobial activity against enterohemorrhagic Escherichia coli and Listeria monocytogenes clinical isolates, among other pathogenic bacteria. Therefore, Ent35?MccV may find important applications in food or pharmaceutical industries.